IMPLEMENTTION OF THE DISCUSSION METHOD IN STRENGTHENING STUDENTS' UNDERSTANDING OF FIQH (CASE STUDY AT MA. MISBAHUL FATA KLENANG KIDUL BANYUANYAR PROBOLINGGO) - M Mahbubi; Farah Najwa Ahmad Puad; Moh. Abdullah Kafa Bihi (International Journal of Multidisciplinary Reseach, 2025)
This study explores the application of the discussion method in enhancing students’ understanding of Fiqh at MA Misbahul Fata Banyuanyar Probolinggo. The research aims to evaluate how this student-centered teaching approach contributes to improved student engagement, critical thinking, and overall learning outcomes. The study employs a qualitative approach using classroom observations, interviews with teachers and students, and document analysis. The findings indicate that the discussion method creates a more dynamic and interactive learning environment, where students actively participate, share ideas, and collaborate with peers. Students demonstrated improved comprehension of Fiqh topics, as well as enhanced social and communication skills. The teacher’s role in moderating discussions and ensuring equal participation was crucial in the success of the method. Despite occasional challenges related to student participation, the study highlights the effectiveness of the discussion method in fostering a positive and engaging classroom atmosphere. The research provides valuable insights for educators seeking to implement more interactive and student-centered teaching strategies in Islamic education.